On-line derivatization with on-line coupled normal phase liquid chromatography-gas chromatography using the through oven transfer adsorption desorption interface: Application to the analysis of total sterols in edible oils - Toledano, Rosa (2012)
In the present work on-line derivatization is combined with on-line normal phase liquid chromatography-gas chromatography (NPLC-GC) to analyze total sterols in edible oils. The method uses the TOTAD interface with an additional LC injection valve to automatically introduce the derivatization reagent. The derivatization reaction takes place in the adsorbent material located inside the liner of the TOTAD interface. The samples were saponified with potassium hydroxide in an ethanolic solution and the unsaponifiable fraction was extracted with diethyl ether. The extract was then analyzed by online derivatization with on-line NPLC?GC, avoiding the laborious thin layer chromatography and off-line derivatization steps used in the Official European Union (EU) method. The relative standard deviations (RSDs) from the absolute peak area were lower than 14% except for campestanol. No variability in retention time was observed. Limits of detection (LODs) were less than 8.82 mg/kg. Different edible oils were analyzed using the proposed method and the results obtained were compared with those obtained using the Official EU method. There was good agreement between both methods for all the sterols analyzed.